2021
DOI: 10.1093/bbb/zbaa124
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selection of an RNA aptamer yields an interleukin-6/interleukin-6 receptor interaction inhibitor

Abstract: Interleukin-6 (IL-6) binds to the IL-6 receptor (IL-6R) subunit, related to autoimmune diseases and cytokine storm in COVID-19. In this study, we performed systematic evolution of ligands by exponential enrichment and identified a novel RNA aptamer. This RNA aptamer not only bound to IL-6R with a dissociation constant of 200 n m, but also inhibited the interaction of IL-6R with IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…They also demonstrated that their DNA aptamer-gold nanostar conjugate can stop virus infection by blocking the ACE2 receptor-binding capability while destroying the lipid membrane of the virus. Interestingly, Ando et al [ 215 ] propose the use of an IL-6/IL-6 receptor interaction inhibitor as a possible therapeutic against COVID-19. The IL-6 binding to the IL-6R sub-unit has been implicated in cytokine storm occurrence in the COVID-19 pathology.…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that their DNA aptamer-gold nanostar conjugate can stop virus infection by blocking the ACE2 receptor-binding capability while destroying the lipid membrane of the virus. Interestingly, Ando et al [ 215 ] propose the use of an IL-6/IL-6 receptor interaction inhibitor as a possible therapeutic against COVID-19. The IL-6 binding to the IL-6R sub-unit has been implicated in cytokine storm occurrence in the COVID-19 pathology.…”
Section: Discussionmentioning
confidence: 99%